PERANCANGAN DASHBOARD IT STRATEGY PLANNING DAN ARCHITECTURE DENGAN PENDEKATAN EAP DAN SWOT - Permatasari, Nastiti Tri; Tjhe, Jap Wie; Irwansyah, Irwansyah; Budiyantara, Agus (Computatio : Journal of Computer Science and Information Systems, 2020)
Bank xyz is the 12th Islamic commercial bank in Indonesia, has the determination to grow millions of Indonesians so that they have a good life according to the bank's slogan, namely To become the best sharia bank, for inclusive finance, changing the lives of millions of Indonesians. The problem in this research is that the process of monitoring and proposing initiatives still uses a manual process. The purpose of this research is to design a system that can meet the need for monitoring and proposing planning initiatives. The research method used is the Enterprise Architecture Planning (EAP) and Strength Weakness Opportunities Treats (SWOT) approaches that integrate information systems and information technology (IS / IT). This study produces a blueprint plan of organizational information in the form of an enterprise architecture that can be used to support policy strategies in system development at xyz islamic bank.